The measurement of capital : the methodology of capital stock estimates in OECD countries - Ward, Michael (Paris : Organisation for Economic Co-operation and Development ; Washington, D.C. : sold by OECD Publications Center, 1976)
The present study relating to the measurement of capital is associated with the analysis of long-term economic growth and productivity trends in OECD Member countries. The report is concerned with the practical problem of what is to be measured by the concept of capital and how it should be measured in different economic contexts.
Includes bibliographical references: p. 142-148.
rpm 04/12/2017
Loans
Keywords: Capital stock